2020
DOI: 10.1038/s41467-020-17822-0
|View full text |Cite
|
Sign up to set email alerts
|

Observation of reduced thermal conductivity in a metal-organic framework due to the presence of adsorbates

Abstract: Whether the presence of adsorbates increases or decreases thermal conductivity in metalorganic frameworks (MOFs) has been an open question. Here we report observations of thermal transport in the metal-organic framework HKUST-1 in the presence of various liquid adsorbates: water, methanol, and ethanol. Experimental thermoreflectance measurements were performed on single crystals and thin films, and theoretical predictions were made using molecular dynamics simulations. We find that the thermal conductivity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
121
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(124 citation statements)
references
References 53 publications
3
121
0
Order By: Relevance
“…Therefore, we will not consider the impact of gas adsorption and guest infiltration, which is known to affect heat transport properties. [ 14 ] We will also disregard interpenetrated systems, even though they often occur for MOF‐508‐type materials. [ 15 ]…”
Section: Figurementioning
confidence: 99%
“…Therefore, we will not consider the impact of gas adsorption and guest infiltration, which is known to affect heat transport properties. [ 14 ] We will also disregard interpenetrated systems, even though they often occur for MOF‐508‐type materials. [ 15 ]…”
Section: Figurementioning
confidence: 99%
“…The low thermal conductivity observed in the present DUTs is close to the value (0.138 -0.174 Wm −1 K −1 ) extracted from their ZIF counterparts, 27,28 but is much smaller than some other SPCs such as MOF-5 (0.31 Wm −1 K −1 ), 24,25 and HKUST-1 (1.65 Wm −1 K −1 ). 33,34 Moreover, it is found that the thermal conductivity of DUT crystals generally decreases with increasing ligand length. For example, when the ligand length increases from one unit of phenylene in DUT-48 to four units of phenylene in DUT-151, the thermal conductivity is found to decline from 0.180 Wm −1 K −1 to 0.071 Wm −1 K −1 .…”
Section: Resultsmentioning
confidence: 99%
“…To data, only the thermal conductivity of some conventional SPCs such as MOF-5, [23][24][25][26] ZIF-8, [27][28][29][30][31][32] and HKUST-1 21,33,34 has been investigated in detail by experimental or computational approaches, while the thermal transport properties of the aforementioned DUT series remain unknown. In addition, the existing studies mainly focus on the influence of gas and water adsorption, 29,34 framework architecture, 24,28,[35][36][37] defects, 33 and physical environment including pressure 18 and temperature 20 on the thermal conductivity of SPCs, little attention has been paid to the evolution of the thermal transport properties of SPCs during their dynamic process, i.e., the phase transition. To the best of our knowledge, there are only two studies regarding the effect of phase transition on the thermal transport in SPCs using MD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…This value is comparable with the other values reported for 2D and 3D MOFs and conductive polymers. [ 21,29–33 ] The contribution from κnormale is proportional to σ (Wiedemann–Franz law) and is, in general, one or two orders of magnitude larger than κnormalp in electrically conductive materials. [ 34 ] Though the device structure of the thermal conductivity measurement prevented us from measuring the electrical conductivity on the same sample, we can deduce that κnormale is negligible compared with κnormalp, considering that the measured thermal conductivity is already close to the theoretical limit of phonon thermal conductivity: the minimum of the phonon mean free path is twice the interatomic distance.…”
Section: Resultsmentioning
confidence: 99%